2010
DOI: 10.1111/j.1365-2850.2010.01594.x
|View full text |Cite
|
Sign up to set email alerts
|

Crime and health: a preliminary study into the effects of crime on the mental health of UK university students

Abstract: In this paper we report on the findings from a preliminary study in the UK into the effects of crime on health. The aim of the study was to investigate what victims of crime report to be the effects of both actual crime and the fear of crime on their physical and psychological health (as well as social well-being) and what actions they take (if any) to deal with these effects. A survey method was adopted using a modified version of the 'Health, Quality of Life and Crime Questionnaire' with 866 undergraduate st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 9 publications
1
18
0
6
Order By: Relevance
“…Although happiness and life satisfaction tap into separate components theoretically, they seem to have similar correlates with fear of crime and in fact have been found to be highly correlated empirically in data from the European Social Survey (for example, Swift et al, 2014). Previous studies have consistently shown that fear of crime is negatively associated with the components of subjective well-being (Hanslmaier, 2013; Michalos and Zumbo, 2000; Moore, 2006; Morrall et al, 2010). …”
Section: Subjective Ill-being As a Consequencementioning
confidence: 90%
“…Although happiness and life satisfaction tap into separate components theoretically, they seem to have similar correlates with fear of crime and in fact have been found to be highly correlated empirically in data from the European Social Survey (for example, Swift et al, 2014). Previous studies have consistently shown that fear of crime is negatively associated with the components of subjective well-being (Hanslmaier, 2013; Michalos and Zumbo, 2000; Moore, 2006; Morrall et al, 2010). …”
Section: Subjective Ill-being As a Consequencementioning
confidence: 90%
“…Informants expected better well-being and health to result from increased employability; in particular, a more stable income, improvement of precarious housing, crime reduction, improvement of hygienic standards, improvement of access to prevention, and improvement of mental resilience. All of these factors have previously been shown to have a positive impact on well-being and health [32,33,34,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Persons who are fearful of victimization report greater distress, particularly depression and anxiety (Norris & Kaniasty, 1994), and are less likely to participate in healthy behaviors, such as walking, and more likely to participate in unhealthy stress-related ones, such as smoking (Pearson & Breetzke, 2014;Ross, 1993). Such effects are not limited to those who have been victimized, but are also observed in nonvictims (Morrall, Marshall, Pattison, & MacDonald, 2010).…”
Section: General Health and Fear Of Crimementioning
confidence: 99%